Effectiveness of Financial Literacy in interest in using QRIS application regarding the challenges of entrepreneurship - anggraeni, oki (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
This research aims to determine the influence of financial literacy on interest in using QRIS on entrepreneurial behavior. The Indonesian Standard QRIS Quick Response Code service supports payment processes from bank and non-bank providers used in the community, making transactions easier. This payment system via QRIS can not only be done in large shopping centers but can also be used in food stalls, tourist attractions, street vendors, even people's markets or traditional markets if they use the QRIS logo. The data source used is primary data with a total of 50 respondents. The analytical method used is descriptive analysis and statistical analysis. From the test results, the results of this research analysis are in accordance with the proposed hypothesis and the direction of the coefficient is consistent, namely a positive effect of 3.058 with a significance of 0.004 which is supported by the data, so it can be concluded that the financial literacy variable has an influence on entrepreneurial behavior, so that an increase of 3.0% will resulting in an increase in the use of MSMEs in entrepreneurial behavior